Synthesis of Sorbitol Fatty Acid Ester through Esterification of Sorbitol and Azelaic Acid Catalysed by Germanium (IV) Oxide - N., Azizan; Chin, S. Y. (2018)
Conventionally, polyurethane (PU) is produced using polyol polyester derived from non-renewable petroleum feedstock. In addition to the restricted resources of petroleum feedstock, inefficient disposal of the non-biodegradable petroleum-based PU waste through landfill and incineration has caused environmental problem. [1]. As an alternative for the current resource, bio-based polyol polyester such as sorbitol fatty acid ester is introduced. Commonly, homogeneous acid catalyst such as sulfuric acid is used in esterification process for the synthesis of polyol polyester [2, 3]. In this study, sorbitol (SL) and azelaic acid (AA) derived from renewable resources were used in the esterification reaction to produce bio-based polyol polyester. Germanium (IV) oxide, a heterogeneous acid catalyst was chosen to eliminate the use of homogeneous acid catalyst that renders corrosiveness, difficulty in the downstream separation and catalyst reuse [4, 5]. The effects of important operating parameters include reaction temperature (160˚C to 220˚C), molar ratio of SL/AA (1:1 to 4:1) and catalyst loading (1 to 4 vol%) were investigated. The reaction was carried out in a batch reactor and the products were analyzed for its acid value through titration and concentration sorbitol and its anhydrides through gas chromatography (GC).